Pulmonary Aspergilloma Co-Existing with Pulmonary Tuberculosis: A Case Report in Type 1 Diabetes Mellitus (T1DM) Patient - Kirana, Widya Tria; Faisal, Hana Khairina Putri; Kitagawa, Hiroki; Setiawan, Gigih; Yunus, Faisal (Faculty of Medicine Universitas Airlangga, 2023)
Introduction: Pulmonary aspergilloma is a disease frequently found in immunocompromised patients. In Indonesia, around 18% of diabetes mellitus (DM) patients suffer from chronic pulmonary aspergilloma. However, data on type 1 DM (T1DM) are still limited. Case: We presented the case of a 22-year-old male admitted to the emergency room due to hemoptysis of approximately 200 ml within six hours before admission, nonspecific chest pain during cough, fever, night sweats, and weight loss of 3 kg over the last months. The patient had a history of T1DM and no prior history of respiratory diseases. Physical examination showed tachycardia, tachypnoea, subfebrile, normal body mass index, and rhonchi on the left thorax. Routine laboratory tests revealed increased blood sugar level (503 mg/dL) and HbA1c 16.4%. Chest X-ray and high-resolution computed tomography (HRCT) showed a cavity with an opaque lesion, crescent sign, consolidation, and reticulonodular infiltrate on the left lung. Rapid molecular tests, tuberculosis (TB), and serum galactomannan (GM) were negative. The patient was diagnosed with pulmonary aspergilloma, T1DM, and clinical TB. He was treated with fluconazole, insulin, and a fixed-dose combination of anti-TB. The patient refused the surgery procedure. Immediately, the hemoptysis stopped, blood glucose level was normal, and concomitant with weight gain. Conclusion: Due to innate and acquired immunity impairment, T1DM is a risk factor for pulmonary infections, including TB and pulmonary aspergilloma. Chest HRCT may help diagnose fungal balls. Though the patient refused to undergo surgery, administering antifungal, anti-TB drugs, and glucose control as initial treatment presented a good prognosis in the patient.